1993
DOI: 10.1149/1.2221106
|View full text |Cite
|
Sign up to set email alerts
|

Distributions of Cr Depletion Levels in Sensitized AISI 304 Stainless Steel and Its Implications Concerning Intergranular Corrosion Phenomena

Abstract: An electrochemical method has been employed to obtain the population distribution of minimum grain boundary Cr concentrations for sensitized AISI 304 stainless steel ($30400). The detailed information about the extent of Cr depletion provided by the distribution is compared to the average degree of sensitization (DOS) evaluated by the standard and a modified single loop-electrochemical potentiokinetic reactivation (SL-EPR) technique. The distribution of Cr levels on a grain by grain basis is shown to provide i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(27 citation statements)
references
References 11 publications
0
27
0
Order By: Relevance
“…Only when the fraction of random grain boundaries increased beyond 75 pct was the beneficial effect in sensitization, IGC, and IGSCC observed. It has been shown by the bond percolation theory [29] that there is a continuous connectivity of grain boundaries of a particular type (or sensitized boundaries) when the fraction of that type of boundary increases beyond 75 pct. At 75 pct of the boundaries, the random boundaries are continuously connected together by random boundaries.…”
Section: Controlling Sensitization By Increased Fraction Of Randmentioning
confidence: 99%
See 1 more Smart Citation
“…Only when the fraction of random grain boundaries increased beyond 75 pct was the beneficial effect in sensitization, IGC, and IGSCC observed. It has been shown by the bond percolation theory [29] that there is a continuous connectivity of grain boundaries of a particular type (or sensitized boundaries) when the fraction of that type of boundary increases beyond 75 pct. At 75 pct of the boundaries, the random boundaries are continuously connected together by random boundaries.…”
Section: Controlling Sensitization By Increased Fraction Of Randmentioning
confidence: 99%
“…This was confirmed by measurements with a ferrite meter, which showed FN numbers greater than 30. It has been shown that depletion of chromium in alloy 800 [28] and in alloy 600 [29] makes the materials magnetic, and measurements of magnetic susceptibility of these alloys have been correlated [31,32] to degree of sensitization and also to levels of chromium in the chromium depletion zones at grain boundaries. These results show that chromium is selectively removed from the surfaces of alloy 690 in contact with molten glass at 950 °C to 1000 °C.…”
Section: Alloy 690-molten Glass Interactionsmentioning
confidence: 99%
“…2,4,13,[26][27][28] The DL-EPR test was conducted in 0.5% H 2 SO 4 solution with 0.0013 wt% KSCN at 30…”
Section: Double-loop Electrochemical Potentiokinetic Reactivation (Dlmentioning
confidence: 99%
“…Intergranular corrosion of austenitic stainless steels has been explained by the chromium depletion theory [6,7]. It has been shown that the extent of chromium-depleted zones at grain boundaries is a direct indication of the material's susceptibility to IG process, and in the presence of residual stresses and strain to IGSCC as well in the final stage [8].…”
Section: Introductionmentioning
confidence: 99%
“…According to the ASTM standard, metallographic etching and weight-loss tests are regularly performed to assess degree of sensitization (DOS) of austenitic stainless steels (SS) [7][8][9][10][11][12][13][14][15]. These evaluation techniques suffer from either a long testing period or requirement of a large amount of etchant.…”
Section: Introductionmentioning
confidence: 99%